(untitled) (Community Based Medical Journal, 2022)
A cross-sectional, descriptive study was conducted in Community Based Medical College, Bangladesh (CBMC,B) Hospital during August and September 2018 to identify knowledge, attitude and practice regarding diet among pregnant women attending antenatal checkup. This study was done as a part of Residential Field Site Training by 3rd year MBBS students under Community Medicine curriculum. Data were collected on a predesigned questionnaire by direct interviewing a total of 116 pregnant women. Data analysis was done by SPSS version 20.0. Age distribution of respondents ranged from 18 years to 35 years; mean age 24.45±4.69 years. Most of the respondents 99(85.34%) belonged to age group 18 years to 29 years. Most of them were Muslim 99(85.34%), literate 93(80.17%), and housewives 96(82.76%), belonged to middle class family 65(56.03%). 46(39.66%) were found at risk, based on risk assessment. Knowledge regarding diet and nutrition was found in optimum level. Majority 55(47.41%) had excellent score, while 49(42.24%) had good score and 12(10.34%) were not up to the mark. Attitude of family members regarding care of pregnant woman was positive in most cases, 113(97.41%). Majority 55(47.41%) had excellent dietary practice, 23(19.83%) were good and 38(32.76%) were bad. Barriers of implementation of good dietary practice include lack of knowledge 12(10.34%), poverty 17(14.66%) and lack of cooperation from husband and in-laws 9(7.76%). CBMJ 2022 January: vol. 11 no. 01 P: 46-51